Current Challenges in the Identification of Pre-Erythrocytic Malaria Vaccine Candidate Antigens - Bettencourt, Paulo (Frontiers in Immunology, 2020)
Plasmodium spp.-infected mosquitos inject sporozoites into the skin of a mammalian host during a blood meal. These enter the host’s circulatory system and establish an infection in the liver. After a silent metamorphosis, merozoites invade the blood leading to the symptomatic and transmissible stages of malaria. The silent pre-erythrocytic malaria stage represents a bottleneck in the disease which is ideal to block progression to clinical malaria, through chemotherapeutic and immunoprophylactic interventions. RTS,S/AS01, the only malaria vaccine close to licensure, although with poor efficacy, blocks the sporozoite invasion mainly through the action of antibodies against the CSP protein, a major component of the pellicle of the sporozoite. Strikingly, sterile protection against malaria can be obtained through immunization with radiation-attenuated sporozoites, genetically attenuated sporozoites or through chemoprophylaxis with infectious sporozoites in animals and humans, but the deployability of sporozoite-based live vaccines pose tremendous challenges. The protection induced by sporozoites occurs in the pre-erythrocytic stages and is mediated mainly by antibodies against the sporozoite and CD8+ T cells against peptides presented by MHC class I molecules in infected hepatocytes. Thus the identification of malaria antigens expressed in the sporozoite and liver-stage may provide new vaccine candidates to be included, alone or in combination, as recombinant protein-based, virus-like particles or sub-unit virally-vectored vaccines. Here I review the efforts being made to identify Plasmodium falciparum antigens expressed during liver-stage with focus on the development of parasite, hepatocyte, mouse models, and resulting rate of infection in order to identify new vaccine candidates and to improve the efficacy of the current vaccines. Finally, I propose new approaches for the identification of liver-stage antigens based on immunopeptidomics.